THE DETERMINATION OF SUGARS BY CHROMATOGRAPHIC METHOD - Sri Sumartini; Julia Kantasubrata (Research Center for Chemistry - LIPI, 1992)
Experiments have been carried out to analyse sugars using TLC and HPLC methods, In the TLC method, separation of sugars was performed on silica plates impregnated with monosodium phosphate and using mixture of ethylacettuel pyridinde/water as an eluent. Whilst in the HPLC method, the use of three column types i.e. diol, RP-18 and modified silica column were tested. The results showed that TLC method was able to measure three sugars i:e. sucrose, glucose and fructose with standard deviations of 11.6%, 7,6% and 1,9%, respectively. On the other hand, the HPLC method with silica column modified by polyamine and compressed with WATERS RCM-l00, showed the best results, in which mixtures of nine sugars were well separated and measured quantitatively with good precisian.